An Analysis of High Order Thinking Skills Aspects on the Assessment Instruments in Ecosyst Topic for the 10th Grade Senior High School Students - Anisha S; Indra Hartanto; Yuni Ahda; Rahmawati Darussyamsu (ATRIUM PENDIDIKAN BIOLOGI, 2020)
This research is an description  research which aims to see the influence of higher order thinking skills in biological learning  at SMAN 1 Nan Sabaris. Higher order thinking skills are essential for student future. The future demands the existence of an evoluation instrument to train student higher order thingking, not only the thinking skill in the lower cognitive domain, but also in a higher domain. One of the efforts to enhance higher order thinking skills is to engage studenta with the question integrade by cognitive C4-C6. The research analysed aspect of higher order thinking in an evaluation instrument. Evaluatio9n instrument used by teachers at schools are still in the C1-C4 cognitive level (C1 17%, C2 35%, C3 26%, C4 22%), the evaluation instrument are not eligible according to the standart applied. The low cognitive level obtained in the evaluation instrument used by the teachers is the reason of the low thinking level of the student.    Higher Order Thinking Skills, Evaluation Instrument